ABORTUS DAN MENSTRUAL REGULATION - Saiful Saiful (Islam Futura, 2008)
Henomenons about abortus and menstrual regulation during the time, especially in Indonesian have been cultured. Likely society assumes the abortus and this menstrual regulation as habit problem which needn't be disputed. Is it right? How also rule of law of concerning practice about abortus and menstrual regulation according to Islam view as well as KUHP (Criminal Code) in Indonesian. Likely, the problem do not only concerning just doctor problem, but ecause the practice of abortus and this menstrual regulation is instructed to criminal action, hence require to be straightened by opening some opinion of fiqh expert.